2016
DOI: 10.17576/mjas-2016-2006-27
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cadmium (Ii) Ions by Polyacrylonitrile-Based Activated Carbon Nanofibers/Magnesium Oxide as Its Adsorbents

Abstract: In this work, activated carbon nanofibers (ACNFs) from precursor polyacrylonitrile (PAN) and magnesium oxide (MgO) were prepared via electrospinning process. The morphological properties of the PAN/MgO-based ACNFs were characterized by using Scanning Electron Microscopy (SEM) and the specific surface area (SSA) were investigated using nitrogen adsorption, Brunauer-Emmett-Teller (BET) methods. Moreover, the functional groups were analyzed by using Fourier Transform Infrared (FTIR). Besides that, the sorption st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This in turn increases the total SSA and improves adsorption performance on the surface of ACNFs. In this study, Yusof et al 77 found that Cd(II) adsorption on MgO-ACNFs is higher than pure ACNFs and granular activated carbon (GAC).…”
Section: The Adsorptive and Degradative Capabilities Of Mgo Nanoparti...mentioning
confidence: 63%
“…This in turn increases the total SSA and improves adsorption performance on the surface of ACNFs. In this study, Yusof et al 77 found that Cd(II) adsorption on MgO-ACNFs is higher than pure ACNFs and granular activated carbon (GAC).…”
Section: The Adsorptive and Degradative Capabilities Of Mgo Nanoparti...mentioning
confidence: 63%